Clinical outcomes following intra-articular injection of autologous adipose-derived mesenchymal stem cells for the treatment of osteoarthritis in dogs characterized by weight-bearing asymmetry. Issue 10 (1st October 2021) - Sanghani-Kerai, Anita; Black, Cameron; Cheng, Shuliang Oliver; Collins, Laura; Schneider, Nadine; Blunn, G.; Watson, Fraje; Fitzpatrick, Noel
Abstract : Aims: This study investigates the effects of intra-articular injection of adipose-derived mesenchymal stem cells (AdMSCs) and platelet-rich plasma (PRP) on lameness, pain, and quality of life in osteoarthritic canine patients. Methods: With informed owner consent, adipose tissue collected from adult dogs diagnosed with degenerative joint disease was enzymatically digested and cultured to passage 1. A small portion of cells (n = 4) surplus to clinical need were characterized using flow cytometry and tri-lineage differentiation. The impact and degree of osteoarthritis (OA) was assessed using the Liverpool Osteoarthritis in Dogs (LOAD) score, Modified Canine Osteoarthritis Staging Tool (mCOAST), kinetic gait analysis, and diagnostic imaging. Overall, 28 joints (25 dogs) were injected with autologous AdMSCs and PRP. The patients were followed up at two, four, eight, 12, and 24 weeks. Data were analyzed using two related-samples Wilcoxon signed-rank or Mann-Whitney U tests with statistical significance set at p < 0.05. Results: AdMSCs demonstrated stem cell-like characteristics. LOAD scores were significantly lower at week 4 compared with preinjection (p = 0.021). The mCOAST improved significantly after three months (p = 0.001) and six months (p = 0.001). Asymmmetry indices decreased from four weeks post-injection and remained significantly lower at six months (p = 0.025). Conclusion: These improvements in quality of life, reduction in pain on examination, and improved symmetry in dogs injected with AdMSCs and PRP support the effectiveness of this combined treatment for symptom modification in canine OA for six months. Cite this article: Bone Joint Res  2021;10(10):650–658.